1969
DOI: 10.1093/genetics/61.2.497
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF EPISTASIS ON HOMOZYGOUS VIABILITY DEPRESSION IN DROSOPHILA MELANOGASTER

Abstract: HIS study was carried out in an attempt to assess the importance of epistasis in the deleterious effects of homozygosity. The experimental procedure utilized mating systems, which have now become standard, whereby chromosomes from natural populations of Drosophila melanogaster are extracted and made homozygous. Interaction between chromosomes was measured by comparison of the viability of flies simultaneously homozygous for the two major autosomes with flies homozygous for one or the other. At the same time, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…5007 The D: L ratio is 0.667. This figure agrees very well with the results for other populations obtained by different investigators: 0.636 by TEMIN et al (1969), and 0.584 by KOSUDA (1971) in D. melanogaster, but is slightly smaller than the value obtained in D. pseudoobscura ( D : L = 0.855) by WILLS (1966). These D: L ratios were calculated with respect to the average viability of the population.…”
Section: Heterozygotessupporting
confidence: 92%
See 1 more Smart Citation
“…5007 The D: L ratio is 0.667. This figure agrees very well with the results for other populations obtained by different investigators: 0.636 by TEMIN et al (1969), and 0.584 by KOSUDA (1971) in D. melanogaster, but is slightly smaller than the value obtained in D. pseudoobscura ( D : L = 0.855) by WILLS (1966). These D: L ratios were calculated with respect to the average viability of the population.…”
Section: Heterozygotessupporting
confidence: 92%
“…It has been reported that some isozyme genes show seemingly permanent linkage disequilibria with polymorphic inversions ( MUKAI, METTLER and CHIGUSA 1971). Synergistic interactions between the second and the third chromosomes and among genes within these chromosomes have been reported in homozygous condition using D. melanogaster (TEMIN et al 1969). In the present experiment, it has been shown that the average degree of dominance of "recessive" lethal genes differs according to their genetic backgrounds.…”
Section: Overdominance and Mild Epistasismentioning
confidence: 96%
“…This is expected for reasons analogous to those for which taking only the first term of a Taylor series provides a good estimate. For the partial or complete absence of dominance in genes with small viability effects, see Greenberg & Crow (1960); for the minimum influence of epistasis, see Temin et al (1969). (Greenberg and Temin are the same person, before and after marriage.)…”
Section: Contrasting Viewsmentioning
confidence: 99%
“…We have also not taken epistasis into account. Studies of chromosomes taken from natural populations and made homozygous (TEMIN et al 1969) and of newly accumulated viability mutants (MUKAI 1969) both show evidence of slight synergism for mildly deleterious effects on viability. However, the magnitude of this epistasis is small, especially in high viability chromosomes.…”
Section: Discussionmentioning
confidence: 99%